Culture Loss and Changes after Earthquake-Related Residence Shift - Lawoju, Niraj (Khwopa Journal, 2024)
The Gorkha Earthquake of 2015 had a massive impact on Nepali people’s economic and social life. Beside physical destruction, it caused immense psychological and cultural losses. Many people had to migrate from their land to new places for survival. Some had to leave their original addresses permanently, while many returned to their land after reconstruction. During the course of these events, the imminent cultural and social losses have been overshadowed till date due to over-emphasis on numerical ways of analyzing losses. Bhaktapur was one among many districts heavily affected by the earthquake. Due to densely compact old houses, Bhaktapur lost a lot of physical property along with many people’s lives. As many houses fell down completely, people had to migrate to new places, mostly on the outskirts of the main city area, either permanently or temporarily. As a by-product of this sort of migration, Bhaktapur, a bastion of cultural life, lost part of its intangible cultural heritage as the lifestyle and interconnectivity went through diverse changes. Objective of this paper mainly is to study how after the earthquake 2015 local people from Bhaktapur Municipality area migrated to the new places on the outskirts of the core, they lost the cultural and social affinity towards their habitual cultural and social events. How these migrations created feelings of loss among the cultural practitioners and other ordinary people living cultural life. By using the theory of cultural losses and revitalization, this paper deals how local people after facing havoc of destructive earthquake, tried to adjust the cultural distancing and forming of new circles of cultural practices. It studies how traditional cultural practices lost their tempo as people from certain neighborhoods (tole/galli) within Bhaktapur’s core area migrated to different places and lost their interconnectivity. This study has shown how cultural changes and losses have accelerated in Bhaktapur after the earthquake and how people who migrated to the outskirts are trying to build up cultural ties with their root with contextualization of cultural losses and changes. This paper is a qualitative study that uses data from field visits, observations and interviews. Highlighting the impact of cultural losses and changes, the paper suggests some possible ways to revitalize and rejuvenate the cultural life and sustainability of people migrated to the outskirts from the core settlement of Bhaktapur. It also studies how practical ways of cultural adaption are being used amidst the vulnerability of cultural losses. Findings of this paper are significant to understand the intangible losses resulted because of the earthquake besides seen tangible losses. It is importantly significant to understand the dynamism of cultural changes and cultural differences. This study could help to understand the trend of cultural losses and work to mend and make adjustment of such changes.